From weed biology to successful control: an example of successful management of Ludwigia grandiflora in Germany. (31st July 2016) - Hussner, A; Windhaus, M; Starfinger, U
Summary: Ludwigia grandiflora (water primrose), a native to the Americas, is one of the most important invasive alien aquatic plants in Europe. In Germany, a first population was found in an oxbow lake of the River Leda in Lower Saxony, north‐western Germany, in 2004. Ludwigia grandiflora formed both dense monospecific patches and mixed stands with native plants. A study on the biology of L. grandiflora documented that the plants regrow in spring from vegetative means only, even though viable seed production occurred. Hand weeding was successfully tested in different sampling sites as a sustainable management tool and subsequently used for the management of this species. Within 3 days, more than 99% of the biomass (25 tonnes of fresh mass) was harvested in 2013. Afterwards, a one‐day post‐treatment in the same year, two‐one‐day treatments in 2014 and one‐one‐day treatment in 2015 were made to harvest the regrown plants. After the first year, plant regrowth occurred only in one extremely muddy site, while in more than 99% of the water body, L. grandiflora was eradicated. Even though L. grandiflora was not completely eradicated from the water, a total eradication seems achievable within the next few years. The study documented the difficulties in the management of aquatic weeds, particularly in heterogeneous habitats with varying sediment structure. Management measures must be adapted to the infested habitat and species biology, which is mandatory for successful management of all aquatic weeds.